BUSINESS-LAW TRAINING FOR STUDENTS OF ACCOUNTING. - Dohr, James L. (The Accounting Review, 1938)
Abstract The article focuses on business-law training for students of accounting. Faced with the ever increasing complexities of modem civilization, society has relied very largely on the device of specialization for the solution of its problems. This specialization has given rise to a problem of its own, and without in any way detracting from the splendid achievements of specialists, venture to suggest that there is a serious need in the social organization of today for the coordination of the activities of the various specialists. The respective problems of the legal and accounting professions indicate the author's point, and because of the close relationship between the two professions in certain lines of endeavor, it is essential that the respective viewpoints of the two professions be coordinated. This necessity has been universally recognized in the inclusion of law study in the curricula in the schools of business administration, and recognize to a certain extent by a display of interest on the part of law schools in the teaching of accounting.